2016
DOI: 10.1093/asj/sjw138
|View full text |Cite
|
Sign up to set email alerts
|

Is Office-Based Surgery Safe? Comparing Outcomes of 183,914 Aesthetic Surgical Procedures Across Different Types of Accredited Facilities

Abstract: Accredited OBSS appear to be a safe alternative to ASCs and hospitals for cosmetic procedures. Plastic surgeons should continue to triage their patients carefully based on other significant comorbidities that were not measured in this present study. LEVEL OF EVIDENCE 3.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(36 citation statements)
references
References 30 publications
2
34
0
Order By: Relevance
“…As a result, it makes sense that most research has been exploratory, relying on case studies of adverse events from state registries [ 4 10 , 29 ] or bringing together compilations of data sources [ 11 , 12 ]. The limitations of these studies have been noted in more recent research (e.g., [ 14 ]. But such studies are important first steps in determining if there is a patient safety problem that may be due to facility type or facility characteristics and, if so, what intervention research might be needed to develop evidence-based solutions.…”
Section: Discussionmentioning
confidence: 99%
“…As a result, it makes sense that most research has been exploratory, relying on case studies of adverse events from state registries [ 4 10 , 29 ] or bringing together compilations of data sources [ 11 , 12 ]. The limitations of these studies have been noted in more recent research (e.g., [ 14 ]. But such studies are important first steps in determining if there is a patient safety problem that may be due to facility type or facility characteristics and, if so, what intervention research might be needed to develop evidence-based solutions.…”
Section: Discussionmentioning
confidence: 99%
“…The findings were encouraging with complication rates of less than 2%, suggesting that these facilities are safe for appropriately selected patients by qualified providers. [38][39][40][41] Soltani et al, in an analysis of outcomes on all procedures performed in American Association for Accreditation of Ambulatory Surgery Facilities (AAAASF) from 2001 to 2012, showed postoperative bleeding or hematoma to be the most common complication with a hospital admission rate of 0.2%. 42 Our data supports these findings with hematoma rates of 0.6% in office-based surgical suites and 1.0% in accredited surgical centers.…”
Section: Risk Factorsmentioning
confidence: 99%
“…Gupta et al [10] reported that complication rates for office-based day surgery and procedures at ambulatory surgery centres and hospitals are 1.3%, 1.9% and 2.4%, respectively, and concluded that an accredited office-based day surgery is a safe alternative to in-hospital surgery for cosmetic procedures. They included various types of cosmetic surgeries, such as face-lift and rhinoplasty, but not mandibular contouring surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Despite many risks [9] , this procedure is often performed as an office-based day surgery. Recent research showed that office-based procedures (surgical and non-surgical) doubled to approximately 10 million surgeries per year between 1995 and 2005 [10] . The safety of an office-based day surgery is still debatable.…”
Section: Introductionmentioning
confidence: 99%